2022
DOI: 10.1158/1538-7445.sabcs21-p5-13-24
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P5-13-24: Efficacy of first line CDK4/6 inhibitors in HER2-low vs HER2-zero, hormone receptor positive, HER2 negative metastatic breast cancer

Abstract: Introduction: CDK4/6 inhibitors are the standard of care in the vast majority of patients with metastatic breast cancer (MBC) in first line setting. HER2-low expression, defined as IHC score of 1+ or 2+ with negative ISH assay, has been associated with resistance to CDK4/6 inhibitors. This has not yet been explored for advanced disease in the first line setting. We aimed to analyze the efficacy of CDK4/6 inhibitors in this subset of patients compared to HER2-zero tumors. Methods: We identified patients with po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Previous studies suggested an association between HER2-low status and worse PFS in HR + /HER2-negative aBC patients receiving ET + CDK4/6i [3][4][5] . However, these studies were limited by small sample size 4,5 , lack of statistically significant results 5 , or inclusion of patients treated with ET + CDK4/6i as any line of therapy 3,5 .…”
mentioning
confidence: 94%
See 3 more Smart Citations
“…Previous studies suggested an association between HER2-low status and worse PFS in HR + /HER2-negative aBC patients receiving ET + CDK4/6i [3][4][5] . However, these studies were limited by small sample size 4,5 , lack of statistically significant results 5 , or inclusion of patients treated with ET + CDK4/6i as any line of therapy 3,5 .…”
mentioning
confidence: 94%
“…Previous studies suggested an association between HER2-low status and worse PFS in HR + /HER2-negative aBC patients receiving ET + CDK4/6i [3][4][5] . However, these studies were limited by small sample size 4,5 , lack of statistically significant results 5 , or inclusion of patients treated with ET + CDK4/6i as any line of therapy 3,5 . While our findings confirm and expand results of these studies in a larger cohort of patients receiving first-line CDK4/6i, they also provide first evidence that HER2-low status is associated with worse patient OS, which is unlikely to be attributable to the number of subsequent lines of therapy; indeed, in our study patients with HER2-low disease received a higher average number of subsequent lines of systemic therapy when compared to patients with HER2-0 disease after tumor progression to ET + CDK4/6 inhibitors.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…Two previous studies have found that low ERBB2 expression is associated with a poor prognosis in patients with HR-positive mBC treated with CDK4/6is when compared with those who have no ERBB2 expression by immunohistochemical analysis. 12,14 Two other contemporaneous studies showed that low ERBB2 expression did not affect the response to CDK4/6is. 15,16 More data are needed to better understand whether low ERBB2 expression is truly prognostic and whether it merits consideration as a distinct entity, especially in HR-positive mBC, given the contradicting information.…”
Section: Introductionmentioning
confidence: 99%